Bioanalytical RP-HPLC method validation for resveratrol and its application to pharmacokinetic and drug distribution studies - Shivaprasad Gadag, Reema Narayan, Yogendra Nayak, Usha Yogendra Nayak (Journal of Applied Pharmaceutical Science, 2022)
In the present study, an attempt was made to develop and validate a highly sensitive reverse phase-High Pressure Liquid Chromatography (HPLC) method for the quantification of resveratrol (RVT) in the plasma and tissue matrix. Pharmacokinetics and tissue distribution studies were carried out in rats after oral administration of RVT. RVT was eluted using 0.1% orthophosphoric acid and acetonitrile as the mobile phase. The developed method showed good recovery and linearity without any interference from the biological matrix. From the pharmacokinetic studies, the plasma half-life of RVT was found to be 4.4 ± 0.12 hours. It was observed from bio-distribution studies that RVT preferentially accumulated in the high perfused organs. The developed method was successfully applied for the quantification of RVT in different biological matrices.
Keywords: Bioanalytical method, resveratrol, pharmacokinetics, tissue distribution, HPLC